Perlindungan Terhadap Merk Di Indonesia - M Chairul Idrah (Jurnal LEX SPECIALIS, 2011)
In order to cope with imitation products or other works necessary for the protection of intellectual property rights is a legal protection for products or work of any violation that is not in accordance with the agreements and conventions that have been agreed upon. One of the intellectual property rights to be protected is the Brand. Brand Protection is listed preventive and repressive nature Preventive Protection of brand owners to register the legal protections and report instances of violations of Brands. Refresif protection when there is an element of criminal offense Brand or Brand. Brand owners registered to report if there is a resemblance to the Brands They're the speakers listed in accordance with Law number 15 of 2001 with a reported lawsuit at local court Commerce. Key Note : Protection against brand